Employing the Yakir model in achieving and developing deductive thinking among students at the Institute of Fine Arts in the history of Islamic art and ancient civilizations subject. (Journal of the College of Basic Education, 2025)
The current research aims to identify the use of the Yacker model in the achievement and development of deductive thinking among students of the Institute of Fine Arts in the subject of the history of Islamic art and ancient civilizations. The research problem relates to the use of the “Yaker” model to improve students’ achievement and develop their deductive thinking in the subject of the history of Islamic art and ancient civilizations among students. Institute of Fine Arts. Students suffer from poor academic achievement and a lack of inferential thinking skills, which negatively affects their ability to understand and analyze academic material in depth. The study aims to explore the effect of applying the Yacker model on enhancing students’ achievement and developing their reasoning skills, which may contribute to providing innovative and effective educational strategies. The importance of research lies in its ability to improve academic performance and enhance students’ analysis and interpretation skills, which will lead to improving the quality of education in this field. The research objectives include evaluating the impact of the model on achievement and the development of inferential thinking, and providing educational strategies based on the research results. The research includes collecting data through academic tests, questionnaires, and classroom observation, and analyzing it using statistical methods such as variance analysis and descriptive tests. Expectations indicate that applying the Yacker model will lead to a significant improvement in the level of achievement and the ability to think inferentially, which calls for recommendations to enhance the use of the model in teaching and develop training programs for teachers.